Dependence of the Linear Intensity Coefficient of Cosmic Rays Hard Component on the Path Length Through Earth's Atmosphere - Taroyan, A. S.; Kokanyan, E. P.; Mamyan, A. M.
The work examines the dynamics of changes in the intensity of the hard components of cosmic radiation per unit path length, depending on the length of the atmospheric air layer.
Keywords: Physics